Proline-functionalized graphene oxide nanoparticles (GO-Pro NPs): A new engineered nanoparticle to ameliorate salinity stress on grape (Vitis vinifera L. cv Sultana) - Zahedi, Seyed Morteza; Abolhassani, Mohammad; Hadian-Deljou, Marziyeh; Feyzi, Hadis; Akbari, Ali; Rasouli, Farzad; Koçak, Mehmet Zeki; Kulak, Muhittin; Gohari, Gholamreza (My University, 2023)
Salinity stress is of the critical abiotic stress factors in many parts of the world, especially in arid and semi-arid regions and drastically decrease the growth and productivity of the crop. Therefore, in order to maintain the crop productivity and ensure food security in salt-stress suffered regions; in the last decade, novel engineered nanoparticles were synthesized and then assayed for their potential effects concerned with the plant protection against stress conditions. Herewith the present study, we synthesized proline-functionalized graphene oxide nanoparticles (GO-Pro NPs). Then, the interaction effects of either GO-Pro NPs (50 and 100 mg L−1) or graphene oxide nanoparticles (50 and 100 mg L−1) and salinity stress (50 and 100 mM NaCl) on Vitis vinifera L. cv Sultana were evaluated by assaying an array of parameters, viz. photosynthetic pigments, electrolyte leakage, relative leaf water content, protein, proline, antioxidant defense systems, and oxidative stress markers. Accordingly, salinity critically reduced chlorophyll index and content as well as leaf water content, whilst it caused significant increases in electrolyte leakage, the enzyme activity of superoxide dismutase (SOD) as well as contents of proline, malondialdehyde (MDA) and hydrogen peroxide (H2O2). In stress-submitted plants, foliar application of proline-functionalized graphene oxide nanoparticles (100 mM) was effective against oxidative damage with increasing the activity of antioxidant enzymes, proline, and the relative water content of leaves and reducing electrolyte leakage (EL), H2O2, and MDA. The current findings revealed that the oxidative stress caused by salinity in Sultana cultivar grapes might be alleviated by foliar application of different levels of proline-functionalized graphene nanoparticles.
Keywords: Antioxidant enzyme activity; Carbon nanomaterials; Nanotechnology; Photosynthetic pigment; Plant stress